Analisis dan Perancangan Sistem Informasi Pendaftaran Pasien Rawat Jalan di Rumah Sakit Umum Daerah Lagita - Ismail Arifin (Poltekkes Kemenkes Semarang, 2022)
The hospital is one of the health care facilities, according to UURI no. 44 of 2009 concerning hospitals, it is stated that the hospital is a health service institution that provides complete individual health services that provide outpatient, inpatient and emergency services. Along with the development of the technological era, hospitals are experiencing the impact of these developments. Hospitals must have information systems to carry out their business activities. This is stated in PERMENKES No. 82 of 2013 concerning hospitals must have a Hospital Management Information System to carry out patient registration activities both outpatient, inpatient and emergency. In this case the Lagita Regional Unit Hospital is one of the hospitals that organizes business activities in health care facilities, but in its implementation it has not followed the Minister of Health No. 82 of 2013 so that registration activities are still carried out manually using a registration book. Based on the results of initial observations, the impact caused the registered patient data to experience duplication of data, vulnerable to data loss, length of service time and impact on hospital accreditation later. Based on the results of these observations, the researchers will analyze and design an Outpatient Registration Information System at the Lagita Regional General Hospital. later this system can be used to support the process of business activities in the RSUD Lagita.